Identification of High-Risk of Recurrence in Clinical Stage I Non-Small Cell Lung Cancer - Tsutani, Yasuhiro; Shimada, Yoshihisa; Ito, Hiroyuki; Miyata, Yoshihiro; Ikeda, Norihiko; Nakayama, Haruhiko; Okada, Morihito (Frontiers in Oncology, 2021)
Objective This study aimed to identify patients at a high risk of recurrence using preoperative high-resolution computed tomography (HRCT) in clinical stage I non-small cell lung cancer (NSCLC). Methods A total of 567 patients who underwent screening and 1,216 who underwent external validation for clinical stage I NSCLC underwent lobectomy or segmentectomy. Staging was used on the basis of the 8th edition of the tumor–node–metastasis classification. Recurrence-free survival (RFS) was estimated using the Kaplan–Meier method, and the multivariable Cox proportional hazards model was used to identify independent prognostic factors for RFS. Results A multivariable Cox analysis identified solid component size (hazard ratio [HR], 1.66; 95% confidence interval [CI] 1.30–2.12; P < 0.001) and pure solid type (HR, 1.82; 95% CI 1.11–2.96; P = 0.017) on HRCT findings as independent prognostic factors for RFS. When patients were divided into high-risk (n = 331; solid component size of >2 cm or pure solid type) and low-risk (n = 236; solid component size of ≤2 cm and part solid type) groups, there was a significant difference in RFS (HR, 5.33; 95% CI 3.09–9.19; 5-year RFS, 69.8% vs. 92.9%, respectively; P < 0.001). This was confirmed in the validation set (HR, 5.32; 95% CI 3.61–7.85; 5-year RFS, 72.0% vs. 94.8%, respectively; P < 0.001). Conclusions In clinical stage I NSCLC, patients with a solid component size of >2 cm or pure solid type on HRCT were at a high risk of recurrence.